Mechanism and kinetics study on ultrasound assisted leaching of gallium and zinc from corundum flue dust. (15th June 2022) - Ding, Wei; Bao, Shenxu; Zhang, Yimin; Xiao, Junhui
Graphical abstract: Highlights: Ultrasound (US) assisted leaching extracted gallium and zinc from corundum flue dust (CFD). The kinetics of leaching of gallium and zinc from CFD in sulfuric acid is particularly highlighted. The enhanced mechanism of US was explicitly explained. Ultrasound assisted leaching may be a potential industrial technique for recovery of valuable metals from CFD. Abstract: In this study, the effect and mechanism of ultrasound on gallium and zinc leaching from corundum flue dust (CFD) were investigated systematically. The conditions for the leaching of valuable metals were optimized while varying the parameters such as leaching time, sulfuric acid concentration and leaching temperature. It was found that under the conditions of a sulfuric acid concentration of 25 wt%, 90 °C leaching temperature and 50 min leaching duration, the leaching efficiencies of gallium and zinc can be increased from 62.78% to 82.56% and 94.43% to 99.57% as ultrasound was implemented, respectively. The kinetics analysis indicated that the leaching process of gallium from CFD is controlled by mixed of diffusion and chemical reactions, while the leaching process of zinc is controlled by diffusion. The enhancement of ultrasound on the leaching rate and leaching efficiency was mainly ascribed to that the ultrasound effect causes the agglomerates of particles to break into small pieces or generate cracks, which would augment the diffusion of sulfuric acid and the product layer on the particle surface. On the other hand, the reaction of sulfuric acid with amorphous silicate (or aluminosilicate) is accelerated, so that the gallium in the form of encapsulated can be dissolved.